Effects of Muscle Energy Technique with and without Bowen Therapy in Text Neck Syndrome - Pakeeza Seemal, Rabiya Noor, Saba Riaz, Hamna Afzal, Sania Anwaar, Mehwish Niaz, Pakeeza Seemal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the effects of Muscle energy technique with and without Bowen therapy on pain, function, range of movement, and posture in Text neck syndrome. Methods: A randomized clinical trial was conducted in Fatima Hospital Sargodha. A total of 22 patients with text neck syndrome were included and randomly allocated to two groups. Assessment of pain, function, Cervical ROM, Craniovertebral angle, and Rounded shoulder angle was taken using a Numeric pain rating scale (NPRS), Neck disability index (NDI), Goniometer, and photogrammetry. Group A received treatment with hot packs and METs. Group B received a hot pack, Muscle energy technique (METs) and Bowen therapy. A total of 18 sessions were given in 6 weeks with 3 sessions per week. Both groups were reassessed after 3 weeks and 6 weeks of treatment with follow-up after 3 weeks of treatment completion. Data were analyzed by using SPSS 21. Results: Findings revealed that a statistically significant difference (p<0.05) was observed for both within a group and between-group analysis in NPRS, NDI, cervical range of motion (CROM), Craniovertebral angle (CVA), and Rounded shoulder angle (RSA). However, the Bowen group showed more improvement in terms of all outcome measures based on their mean differences. Conclusion: The combination of METs and Bowen therapy was more effective in decreasing pain, improving movement, regaining functional status, and correcting posture in individuals with Text neck syndrome rather than using METs alone.